The Application of Clustering Technique in Teaching Essay Writing to the Students of English Study Program of Riau University - Aruan, Rumiri (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
This study aimed to improve the learning process in essay writing by applying clustering techniques. There were29 students as the subject of this study. The design of the research was One Group Pretest- Posttest. The results of pre - test showed that the studentsâ ability in essay writing was low, only 6.89% of students got good grade, 51.72% got average and, 41.37% of students got low. After applying the clustering technique plus feedback, the learning outcomes was very significant. The percentage of students who obtained excellent score was13.79%, 72.41% was in the good category, 13.79% in the enough category, and no more students got less or failed category. This result showed that the clustering technique plus feedback is worth considering to use in learning writing.